2021
DOI: 10.1001/jamapediatrics.2020.3579
|View full text |Cite
|
Sign up to set email alerts
|

Cannula With Long and Narrow Tubing vs Short Binasal Prongs for Noninvasive Ventilation in Preterm Infants

Abstract: with long and narrow tubing (CLNT) has gained increasing popularity for applying noninvasive respiratory support for newborn infants thanks to ease of use, perceived patient comfort, and reduced nasal trauma. However, there is concern that this interface delivers reduced and suboptimal support. OBJECTIVE To determine whether CLNT is noninferior to short binasal prongs and masks (SPM) when providing nasal intermittent positive pressure ventilation (NIPPV) in preterm infants.DESIGN, SETTING, AND PARTICIPANTS Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Of the 105 studies identified during the systematic search of the literature, a total of six studies were included (RCTs: 3 studies (Maram 2021, Hochwald 2021, and Gokce 2021) ( n = 521); [ 24 , 25 , 26 ] observational studies: 3 studies (Singh 2018, Sharma 2020, Drescher 2018) ( n = 138)) [ 21 , 23 ]. The PRISMA flow is depicted in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 105 studies identified during the systematic search of the literature, a total of six studies were included (RCTs: 3 studies (Maram 2021, Hochwald 2021, and Gokce 2021) ( n = 521); [ 24 , 25 , 26 ] observational studies: 3 studies (Singh 2018, Sharma 2020, Drescher 2018) ( n = 138)) [ 21 , 23 ]. The PRISMA flow is depicted in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flow is depicted in Figure 1 . The three RCTs had enrolled neonates born at a gestational age of 28–34 weeks [ 24 , 25 , 26 ]. Two of the RCTs (Gokce 2021 and Hochwald 2021) [ 24 , 25 ] used NIPPV as the NRS modality, and one (Maram 2021) used CPAP [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is concern that this interface delivers reduced and suboptimal support. In a noninferiority randomized clinical trial 6 that included 166 preterm infants at 24 weeks’ to 33 weeks and 6 days’ gestation requiring NIPPV, intubation within 72 hours occurred in 14% in the group using RAM cannula and in 18% in the short binasal prongs and masks group (95% CI within the noninferiority margin). Moderate to severe nasal trauma was significantly less common in the group using cannulas with long and narrow tubing.…”
Section: Neonatal Lung Diseasesmentioning
confidence: 99%
“…While Hochwald et al made a similar comparison for preterm neonates receiving NIPPV 12 , there are no adequately powered studies that compared these two interfaces in reducing nasal injuries. As previous physiological and in vivo studies 13 17 demonstrated concerns on the efficacy of RAM cannula to deliver the set pressures, we used Cannulaide, a hydrocolloid protective barrier which secures cannula in place and provides a seal, in RAM cannula group for snugly fitting the nasal cannula, preventing leak and allowing better delivery of CPAP pressures.…”
Section: Introductionmentioning
confidence: 99%